1999
DOI: 10.1038/46587
|View full text |Cite
|
Sign up to set email alerts
|

CtBP/BARS induces fission of Golgi membranes by acylating lysophosphatidic acid

Abstract: Membrane fission is essential in intracellular transport. Acyl-coenzyme As (acyl-CoAs) are important in lipid remodelling and are required for fission of COPI-coated vesicles. Here we show that CtBP/BARS, a protein that functions in the dynamics of Golgi tubules, is an essential component of the fission machinery operating at Golgi tubular networks, including Golgi compartments involved in protein transport and sorting. CtBP/BARS-induced fission was preceded by the formation of constricted sites in Golgi tubul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
269
2

Year Published

2000
2000
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 310 publications
(273 citation statements)
references
References 23 publications
2
269
2
Order By: Relevance
“…CtBP/BARS is an adaptor protein initially identi®ed through its ability to interact with and inhibit the tumorigenic activity of adenovirus E1A (Schaeper et al, 1995). CtBP/BARS binds to cell cycle and transcriptional regulatory complexes (Meloni et al, 1999;Sewalt et al, 1999;Sollerbrant et al, 1996) but it also controls membrane vesiculation in the Golgi complex (Weigert et al, 1999). Parallels between CtBP and Bin1 are intriguing given their connections to E1A and c-Myc, which are biologically distant cousins.…”
Section: Bin1 Functionmentioning
confidence: 99%
“…CtBP/BARS is an adaptor protein initially identi®ed through its ability to interact with and inhibit the tumorigenic activity of adenovirus E1A (Schaeper et al, 1995). CtBP/BARS binds to cell cycle and transcriptional regulatory complexes (Meloni et al, 1999;Sewalt et al, 1999;Sollerbrant et al, 1996) but it also controls membrane vesiculation in the Golgi complex (Weigert et al, 1999). Parallels between CtBP and Bin1 are intriguing given their connections to E1A and c-Myc, which are biologically distant cousins.…”
Section: Bin1 Functionmentioning
confidence: 99%
“…71 In isolated Golgi apparatus the CtBP3 isoform (previously known as BARS, Brefeldin A-ADP Ribosylated Substrate, and recently renamed as short-CtBP1 or CtBP1-S) has been shown to be a key component of the machinery controlling Golgi tubule fission. 72 In recent studies on intact cells, the CtBP fission inducing activity was shown to participate in the fragmentation of the Golgi complex during mitosis 73 as well as in intracellular membrane traffic. 74 Recently, a combined approach based on bioinformatics, NMR, CD spectroscopy, and small-angle X-ray scattering that was applied to analyze CtBP structure demonstarted that 90 C-terminal residues of this protein are intrinsically unstructured in the full-length CtBP and in constructs lacking the substrate-and/or the nucleotide-binding domains.…”
Section: Cellular Components Associated With Intrinsically Disorderedmentioning
confidence: 99%
“…56 BARS is the short splice variant of CtBP1-L, and both isoforms have been shown to exhibit a dual function as transcriptional co-repressors in the nucleus and Golgi membrane fission in the cytoplasm. [57][58][59][60] CtBP/BARS-mediated membrane fission has been implicated in many intracellular trafficking steps, including polarized transport from the Golgi apparatus to the basolateral plasma membrane and Golgi-ER retrograde transport (reviewed in ref. 60).…”
Section: The Golgi Mitotic Checkpoint Is Regulated By the Golgi Ribbomentioning
confidence: 99%